Metanarrative reflection on life plot structure in English and Russian biographical narrative - Leon, Olga V. (Journal of the Belarusian State University. Philology, 2026)
The object of the given study is metanarrative-level lexical markers that conceptualise key structural components of a life plot. The author seeks to identify both general and culture-specific characteristics of verbal representation of plot structure within biography, to determine the scope of lexical-semantic means, and to describe the nature of the metaphorisation of plot structure metamarkers. For the first time, a comparative analysis of quantitative and qualitative characteristics of the most frequent English and Russian metanarrative plot structure markers is undertaken, as well as the mechanisms of verbal representation of events in different narrative traditions are revealed. The value of the findings lies in clarifying cross-linguistic patterns and culture-bound components of narrative composition, which can be applied in linguistic and philological text analysis, cross-cultural communication, and translation theory.